Hardware Trojan Detection Technique Using Frequency Characteristic Analysis of Path Delay in Application Specific Integrated Circuits - Tran, Ha Thai; Hoang, Phuc Van; Do, Tuan Ngoc; Nguyen, Duong Hai (Journal of Science and Technology on Information security, 2020)
Abstract— Since the last decade, hardware Trojan (HT) have become a serious problem for hardware security because of outsourcing trends in Integrated Circuit (IC) manufacturing. As the fabrication of IC is becoming very complex and costly, more and more chipmakers outsource their designs or parts of the fabrication process. This trend opens a loophole in hardware security, as an untrusted company could perform malicious modifications to the golden circuit at design or fabrication stages. Therefore, assessing risks and proposing solutions to detect HT are very important tasks. This paper presents a technique for detecting HT using frequency characteristic analysis of path delay. The results show that measuring with the frequency step of 0.016 MHz can detect a HT having the size of 0.2% of the original design. Tóm tắt— Từ thập niên 2010, Trojan phần cứng (HT) đã trở thành một vấn đề nghiêm trọng đối với bảo mật phần cứng, do xu hướng thuê sản xuất mạch tích hợp (Integrated Circuit - IC). Khi quá trình chế tạo IC trở nên phức tạp và tốn kém, ngày càng nhiều nhà sản xuất chip lựa chọn phương án thuê lại một phần hoặc toàn bộ thiết kế IC. Xu hướng này tạo ra lỗ hổng trong bảo mật phần cứng, vì một công ty không đáng tin cậy có thể thực hiện các sửa đổi độc hại vào trong mạch nguyên bản ở giai đoạn thiết kế hoặc chế tạo. Do đó, đánh giá rủi ro và đề xuất giải pháp phát hiện HT là một trong những nhiệm vụ hết sức quan trọng. Bài báo này trình bày một giải pháp phát hiện HT sử dụng phân tích đặc tính tần số của độ trễ đường truyền tín hiệu. Kết quả cho thấy, thực hiện khảo sát với bước tần số 0,016 MHz có thể phát hiện được HT có kích thước 0,2% so với thiết kế ban đầu.